Economic Recession in Nigeria: Can Business Education come to the Rescue? - Owenvbiugie, Robinson Osarumwense; Osigbeme, Justina Toristsemofe (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
The study assessed the extent to which business education could reduce absolute poverty, unemployment and environmental degradation. The study adopted a survey design and sampled 111 business educators in four colleges of education in Delta State. Three research questions were raised and a structured questionnaire of 15 items was used to obtain information from the respondents. The results were analyzed via the descriptive statistics of mean and standard deviation. Cronbachâ€™s alpha measurement technique was used to determine the reliability of the instrument which yielded a reliability coefficient of 0.77.  The findings of the study showed that business education can reduce the rising rates of absolute poverty and unemployment in Nigeria to a high extent, but is ineffective to address environmental degradation in Nigeria. Based on these findings, it was recommended amongst others, that Government, non-governmental organizations and stakeholders in the education sector should adequately fund business education programmes in Nigeria for sustainable economic growth and development. Keywords: Economic recession, business education, unemployment, poverty, environmental degradation